KEMAMPUAN PSIKOMOTOR SISWA PADA MATA PELAJARAN SAINS MELALUI PENERAPAN PERANGKAT PEMBELAJARAN SAINS BERBASIS HUMANISTIS - Sudarto Sudarto (Bajang Institute, 2023)
This research is a pre-experimental study with a One-Shot Case Study research design which aims to describe the students' psychomotor abilities in the learning Science through the application of Humanistic Science-Based Learning Devices. Respondents in this study were the students VII.3 grade of SMPN 24 Makassar in amount to 30 people. The research instrument used was the Test Result Recording Sheet. The data collected was the test result data. Data were analyzed using SPSS version 25.0. The results research showed that the number of students (respondents) who obtained abilities in the